2008
DOI: 10.1016/j.psyneuen.2007.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous neurotensin is involved in estrous cycle related alterations in prepulse inhibition of the acoustic startle reflex in female rats

Abstract: SummaryOvarian hormones regulate prepulse inhibition (PPI) of the acoustic startle reflex. Results from studies in intact female rodents investigating sex, estrous cycle and ovarian hormone regulation of PPI are inconsistent. In experiment #1, we investigated whether PPI in female rats is influenced by the time of day of testing and the estrous cycle stage of the rat. PPI was examined across the day of proestrus (P) and diestrus 1 (D1) in female rats and compared to males. PPI in males and P females was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…These findings indicate that not only did the time of day of testing affect PPI, but also these differences cannot be attributed to differences in startle behaviour. While some studies (Kinkead et al, 2008;Frankland and Ralph, 1995;Chabot and Taylor, 1992) have reported an increase in startle amplitude when testing animals during the dark cycle rather than the light cycle, others found no difference (Weiss et al, 1999), as was the result in this study.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…These findings indicate that not only did the time of day of testing affect PPI, but also these differences cannot be attributed to differences in startle behaviour. While some studies (Kinkead et al, 2008;Frankland and Ralph, 1995;Chabot and Taylor, 1992) have reported an increase in startle amplitude when testing animals during the dark cycle rather than the light cycle, others found no difference (Weiss et al, 1999), as was the result in this study.…”
Section: Discussionsupporting
confidence: 57%
“…Circadian fluctuations in hormones including corticosterone and adrenocorticotropin (Atkinson and Waddell, 1997) could be one such variable that interacts with estrous cycle. Kinkead et al (2008) have recently reported on the contribution of endogenous neurotensin to significant time of day effects on PPI in diestrous, females. The effects of estrous cycle however, can be minimized when PPI is assessed at a consistent time of day as reported here; within the window of 2-4 h following the onset of the dark phase of the light/dark cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However in 1998, Koch found no difference in PPI between male and female rats, but PPI was reduced in female rats during prooestrous, in comparison with oestrous and dioestrous phases of the cycle (Koch, 1998). Other researchers have found opposite results, such as higher PPI in male and female rats in prooestrous, in comparison with female rats in dioestrous (Kinkead et al, 2008) or no differences across the oestrous cycle (Adams et al, 2008). These discrepancies have been attributed to different testing conditions, such as stimulus intensity and testing during the light or dark phase.…”
Section: Icssmentioning
confidence: 93%
“…The acoustic startle reflex test was performed six days after the last maternal aggression stressor as previously described [25]. Briefly, during the light cycle, rats were placed in a ventilated startle chamber (San Diego Instruments, San Diego, CA) using an accelerometer to measure the startle reflex.…”
Section: Methodsmentioning
confidence: 99%